The Behavior of Searching for Covid-19 Vaccine Information in Supporting Vaccination Decision-Making - Mirnawati Ahaya; Yudi Perbawaningsih (INJECT (Interdisciplinary Journal of Communication), 2023)
This research aims to analyze the information-seeking behavior of the COVID-19 vaccine in supporting decision-making in the community of Nglanggeran Village, Gunung Kidul Regency, Yogyakarta Special Region. This study provides benefits for the government, especially health workers, to better understand the behavior of the community in seeking information on the COVID-19 vaccine, and vaccination decision-making. The qualitative research method was used with 16 informants consisting of semi-structured interviews and using source triangulation. The results showed that the stages in searching for COVID-19 vaccine information in the Nglanggeran Village community include; starting, chaining, browsing, differentiating, verifying, and sharing. Poor network connections and the geographical conditions of Nglanggeran Village are obstacles for the community in searching for COVID-19 vaccine information. The decision to choose or refuse vaccination is influenced by internal and external factors.